The Geography of Uzbekistan At the Crossroads of the Silk Road - Gulyamova, Lola. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book describes the geography of Uzbekistan and its unique history and culture. It focuses on the development of Uzbekistan as a result of its location on the crossroads of the Silk Road. The influence of global and regional environmental challenges on the current landscape and similar issues are discussed and analyzed from a historical perspective. Contemporary tensions and reforms in social, economical and cultural life are described with the aim to draw a picture of modern paths to transformation and development. The Geography of Uzbekistan includes also information on geology, nature and natural resources, in particular water. The book discusses the social and environmental impacts of the Aral Sea disaster and shows new paths of transformation and development for this Central Asian country.
Acknowledgements -- Preface -- Chapter 1. Introduction -- Chapter 2. Historical Geography -- Chapter 3. Geography of Resources -- Chapter 4. Economic Geography -- Chapter 5. Human Geography -- Chapter 6. Environmental Geography: Nature and Human Interaction -- Index.
Keywords: Geography; Ethnology; Culture; Human geography; Cultural geography; Geology; Regional Geography; Regional Cultural Studies; Social and Cultural Geography; Human Geography; Geology; Geography